Women’s Productivity through Digital Transformation in Local Food Businesses in Fulfilling the Aspects of Maqashid Sharia in Bangsalsari Village, Jember Regency - Wilda Hayatun Nufus; Mahmudah Mahmudah; M.F. Hidayatullah (Eastasouth Institute, 2026)
This study aims to analyze the productivity of women in local food businesses after the implementation of digital transformation and its relevance to the fulfillment of maqashid sharia aspects in Bangsalsari Village, Jember Regency. The study uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The findings indicate that digital transformation through social media, e-commerce, and digital payment systems has significantly increased women’s productivity in terms of product quality, production quantity, marketing effectiveness, and time efficiency. In addition, digital transformation contributes to improving family welfare, expanding market access, and strengthening women’s economic independence. From the maqashid sharia perspective, these improvements reflect the fulfillment of hifz al-mal, hifz al-nafs, hifz al-‘aql, hifz al-nasl, and hifz al-din. The study concludes that digital transformation not only enhances economic productivity but also supports sustainable welfare based on Islamic values.